The medium-chain free fatty acid receptor GPR84 in endometriosis associated pain - Sacher, F; Martinez, F; Zollner, T; Fischer, O; Guo, M; Bafligil, C; Dakin, S; Nagel, J; Zondervan, K; Becker, C; Opermann, U (SAGE Publications, 2018)
The G-protein coupled receptor GPR84 binds and becomes activated by saturated medium-chain free fatty acids, is expressed on pro-inflammatory macrophages and pharmacological inhibition leads to reduction of inflammatory markers.